(3GdeTcdGJ GdbGfhfjI dHWGbI JMbjb GdTNUjI (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdeUQj hGdbGfhf GdaQfSj hGdabg GdESdGej (B/ s - (3eMeO HgGA GdOjf UdGM eMeO SjO LeYI s; (3Cjef SYO Sdjes; (3eMeO jhSa Mafis; (3LGeYI GdbGgQI s (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2017)
(3YGdLJ gPg GdQSGdI GdeTcdGJ GdbGfhfjI GdeJYdbI HGdHjGfGJ GdJj JQO HHWGbGJ JMbjb GdTNUjI GdeUQjI hHWGbGJ GdoghjI GdhWfjI GdaQfSjI, Yf WQjb GdebGQfI Hjf GdbGfhfjf GdeUQj hGdaQfSj hGdabg GdESdGej, MjK ChQO aUdgG GdJegjOj JYQja HWGbGJ JMbjb GdTNUjI heG JDOjg ef hXGFna hegGe, hJJHY hSGFd EKHGJ GdTNUjI GdbOjeI hUhdkG Edi XghQ gPg GdHWGbGJ heG dMbgG ef JWhQ, hYGdL HGHgG GdChd GdeTcdGJ GdbGfhfjI GdeJYdbI HGdHjGfGJ GdTNUjI GdJj JSJNOe HUhQI CSGSjI Ch ecedI aj JMOjO oghjI MGed GdHWGbI, hgj HjGfGJ(B: (3GdGSe, hGdLfS, hGdUhQI GdTNUjI, hJGQjN GdejdGO, heMd GdEbGeI, hGdegfI, hJYQV HGHgG GdKGfj ddeTcdGJ GdbGfhfjI GdeJYdbI HHjGfGJ GdMGdI, hgj HjGfGJ(B: (3GdMGdI GdSjGSjI, hGdMGdI GdGLJeGYjI, hGdMGdI GdOjfjI(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2017.s
(3HHdjhLQGajG(B: (3UaMGJ (B581-627.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdTNU GdWHjYjs; (3GdGSe GdeOfjs; (3GdTQjYI GdESdGejIs; (3GdbGfhf GdeUQjs; (3GdeTcdGJ GdbGfhfjIs; (3HWGbI JMbjb GdTNUjIs; (3HWGbI GdQbe Gdbhejs; (3EKHGJ GdOjGfIs; (3GdMGdI GdGLJeGYjIs; (3GdeSMjjf GdGQKhPcSs; (3eMd GdEbGeIs; (3HjGf GdejdGOs; (3JZjjQ GdLfSs; (3EKHGJ GdghjIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs